Training PE teachers or promoting sport sciences? The ‘initial’ training of physical education teachers in Switzerland between federalism, universitarisation and sportivisation (1972-1995) - Quin, Grégory (Swiss Journal of Educational Research, 2023)
With this contribution, our ambition is to produce an analysis of the structuration process of initial training for physical education teachers in the decades preceding the establishment of the universities of teacher education, between the first dynamics of the sport sciences’ universitarisation and an accelerating sportivisation, in a singular political framework, with a school branch - physical education - whose governance is partly federal, in a country where schools are cantonal. The timeframe of our investigation starts in 1972 with the implementation of the first federal law supporting gymnastics and sport and extends to the beginning of the 2000s, around the entry into force of the federal law on universities of applied sciences.